Determining foot evaluation done in diabetic in-patients admitted in medical wards and analyzing it through Amit Jain’s triple assessment for foot in diabetes - M. P., Santosh; Jain, Amit Kumar C.; S., Gopal (International Surgery Journal, 2018)
Background: The present study was done to assess the foot evaluation done by the physician in diabetic patients and analyzing it through Amit Jain’s triple assessment for foot in diabetes. Methods: A descriptive retrospective study was done at Rajarajeswari Medical College, Bangalore, Karnataka, India. The study period was from July 2017 to December 2017. All the patients admitted in medical ward with diabetes were studied. Results: A total of 65 patients were included in this study. Majority of patients had diabetes of less than 10 year duration. Around 27.7% who were admitted had some history of foot complaints. However, foot examination was done by physicians only in 7.7% of the cases. It was seen that only 6.2% of the feet were inspected (look component), 1.5% of patients pulses were assessed (Feel component) and none of the patients had their sensation checked (Test component). Ophthalmologist was most commonly consulted specialist (35.4%) for eye evaluation in comparison to surgeon for foot evaluation. Conclusions: Diabetic foot is a common complication of diabetes mellitus and screening of foot is essential to prevent complications and amputation. This study done through Amit Jain’s triple assessment for foot in diabetes showed that foot evaluation was poorly done by physicians.